Antecedents and outcomes of supply chain management in Bangladesh - Mohammed Belal Uddin; Bilkis Akhter (Modern Supply Chain Research and Applications, 2019)
Purpose The purpose of this paper is to investigate the institutional and significant competences that have allowed organizations to employ supply chain management (SCM) practices, the practices of SCM and the benefits of SCM practices for both buyers and suppers. Design/methodology/approach A theoretical model (including hypotheses) has been proposed regarding antecedents, SCM practices and outcomes of SCM. Using purposive sampling method, data were collected from different manufacturing, distributing, wholesaling and retailing organizations. Collected data were analyzed in a principal component analysis and structural equation modeling, including confirmatory factor analysis, and path analysis. Findings The empirical results provided supportive evidences in favor of the hypotheses and theoretical arguments except one hypothesis. This study did not a find positive relationship between organizational compatibility and SCM practices. The study found relationships between mutual trust and SCM practices, communication and SCM practices, and cooperation and SCM practices, which were positive and significant. Again, the relationships between SCM practices and competitive advantages, and SCM practices and long-term orientation and growth were also positive and significant. Practical implications Practitioners could also use the findings to align SCM with business strategy and gain an insight for better utilization of the available resources and technology to perform better. Originality/value This study will provide guidance as to the preconditions that need to be in place in order for a company to implement SCM with its suppliers and customers. It will remind practitioners to stay focused on the ultimate goals of SCM - lower costs, increased customer value and satisfaction, and, ultimately, competitive advantage.
Keywords: 650; Outcomes; Supply chain management; Antecedents; Competitive advantages; Long-term orientation and growth